2010
DOI: 10.1136/bcr.02.2010.2724
|View full text |Cite
|
Sign up to set email alerts
|

Internal jugular phlebectasia in an African adult

Abstract: Jugular vein phlebectasia is a rare venous anomaly commonly presenting as a unilateral neck swelling in children and adults. Its aetiology is unknown and its detection may have increased with availability of better imaging facilities. Due to its rarity, a high index of suspicion is required once other causes of neck swelling are excluded. The few reported cases are mainly in children and non-Africans adults. The authors report the case of a 54-year-old Nigerian woman presenting for the first time with a progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…There is no known sex predilection. It is reported that males are more commonly affected than females [3] [6]. Our cases were females.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…There is no known sex predilection. It is reported that males are more commonly affected than females [3] [6]. Our cases were females.…”
Section: Discussionmentioning
confidence: 62%
“…Our cases were females. Although cases of internal and external jugular vein ectasia have been reported mostly in children and non-African adults, as far as we are aware very few cases has been previously reported in the electronic literature in an African adult especially in woman [3]. The cause of venous ectasia is unknown.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations